Penggunaan Analisis Anggaran sebagai Alat Perencanaan dan Pengendalian Keuangan dalam Perusahaan - Purwanti Purwanti; Talul Alkhandari; Indah Ayu Angraeni; Shafa Naswa Intinsa (Lembaga Pengembangan Kinerja Dosen, 2025)
Budget analysis functions as a strategic tool for planning and controlling corporate finances. Using a literature review with a qualitative descriptive approach, the analysis demonstrates that budgeting supports systematic financial planning, efficient resource allocation, and budget realization monitoring through variance analysis. Proper budget implementation encourages cost efficiency and the achievement of financial objectives. Successful budget management depends on inclusive participation, accurate estimation, internal control systems, and adequate information technology support.